Acute Effect of Oral N-Acetylcysteine on Muscle Soreness and Exercise Performance in Semi-Elite Rugby Players. (4th July 2019) - Rhodes, Kate M.; Baker, Dane F.; Smith, Brett T.; Braakhuis, Andrea J.
ABSTRACT: N-acetylcysteine (NAC) supplementation may enhance performance and reduce soreness from acute, repeated-sprint, high-intensity exercise. Our aim was to investigate whether semi-elite rugby union athletes may benefit. In a randomized block design, 17 semi-elite male rugby players were assigned to receive either 1 g oral NAC ( n = 8) or placebo ( n = 9) for six days. The mean percentage effect of NAC on exercise performance was assessed through completion of a broken bronco exercise test on days 5 and 6 of supplementation. Players self-reported muscle soreness and tolerability to supplements using a modified Muscle Pain and Treatment Satisfaction Questionnaire throughout the supplement duration. NAC produced a likely beneficial performance effect on maximum shuttle sprint time (2.4%; 90% confidence limit ± 4.8%) but was unclear on total time during back-to-back broken bronco tests compared to placebo. NAC had a likely protective effect on subjective muscle soreness during days 1–4 of supplementation (−19% ± 27%) but a very likely harmful effect on days 5 and 6 of supplementation (71% ± 59%). Daily supplementation with 1 g of oral NAC for six days produced no adverse side effects, reduced muscle soreness after one bout of damaging exercise, but increased soreness following the second bout. The performance effects were generally unclear apart from maximal sprint time.